Terrorism and transatlantic relations: threats and challenges - Hof, Tobias; Larres, Klaus (Security, conflict and cooperation in the contemporary world, 2022)
This book explores the development of transatlantic policy on international terrorism and assesses the situation today. It takes an interdisciplinary approach to terrorism and transatlantic relations, bringing together experts from contemporary history, political science, military strategy, psychology, law and security. Looking back to the roots of modern terrorism, from the late 70s to 9/11 and beyond, the volume evaluates how attitudes and approaches have changed over this period. It analyses potential solutions for finding a shared philosophy to counter the threat of transnational terrorism in the US and Europe, against a rapidly changing political landscape. Chapters cover a range of topics, including the psychology of terrorism, online propaganda, domestic terrorism, terrorism and finance and cyber security